The role of urbanization and seasonality on the temporal variability of bird communities - Leveau, Lucas Matias (2012)
This paper explores the effects of urbanization and period of the year on the interannual variability of bird richness, abundance and composition. We expected that the more urbanized areas would have greater stability, and that the stability of bird communities would be higher during the reproductive period. We counted birds on transects in urban, suburban and periurban areas during three consecutive years during the reproductive and non-reproductive periods. We estimated interannual variability of bird species richness by calculating the coefficient of variation (CV), whereas we estimated the interannual variability of community composition by calculating the persistence. We accounted for variability in detection among species and habitats, and for sampling variance. The CV of bird richness and the CV of abundance did not show differences among habitat types and periods. Persistence was higher in urban areas than in suburban and periurban areas in both periods. In urban areas, persistence was higher during the reproductive period. Urbanization favors the stability of bird communities dominated by a few exotic bird species. Seasonality seems to be an important factor determining the degree of persistence in bird communities.